Thermal mechanism in magneto radiated [(Al2O3-Fe3O4)/blood]hnf over a 3D surface: Applications in Biomedical Engineering - Guedri, Kamel; Adnan,; Raizah, Zehba; Eldin, Elsayed Tag; EL-Shorbagy, M. A.; Abbas, Waseem; Khan, Umar (Frontiers in Chemistry, 2022)
Nanofluids are a new generation of fluids which help in improving the efficiency of thermal systems by improving heat transport rate and extensive applications of this class extensively fall in biomedical engineering, the electronics industry, applied thermal and mechanical engineering, etc. The core concern of this study is to examine the interaction of Al2O3-Fe3O4 hybrid nanoparticles of lamina shaped with blood over a 3D surface by impinging novel impacts of non-linear thermal radiations, stretching, velocity slippage, and magnetic field. This leads to a mathematical flow model in terms of highly non-linear differential equations via nanofluid-effective characteristics and similarity rules. To know the actual behavior of (Al2O3-Fe3O4)/blood inside the concerned region, mathematical investigation is performed via numerical technique and the results are obtained for different parameter ranges. The imposed magnetic field of high strength is a better tool to control the motion of (Al2O3-Fe3O4)/blood inside the boundary layer, whereas, stretching of the surface is in direct proportion of the fluid movement. Furthermore, thermal radiations (Rd) and γ1 are observed to be beneficial for thermal enhancement for both (Al2O3-Fe3O4)/blood and (Al2O3)/blood.